2021
DOI: 10.3389/fphys.2021.619688
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cervical Sympathetic Chain Input to the Superior Cervical Ganglia Affects the Ventilatory Responses to Hypoxic Challenge in Freely-Moving C57BL6 Mice

Abstract: The cervical sympathetic chain (CSC) innervates post-ganglionic sympathetic neurons within the ipsilateral superior cervical ganglion (SCG) of all mammalian species studied to date. The post-ganglionic neurons within the SCG project to a wide variety of structures, including the brain (parenchyma and cerebral arteries), upper airway (e.g., nasopharynx and tongue) and submandibular glands. The SCG also sends post-ganglionic fibers to the carotid body (e.g., chemosensitive glomus cells and microcirculation), how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 187 publications
(242 reference statements)
2
16
0
Order By: Relevance
“…Four days after bilateral SCGx, the ventilatory parameters at rest remained unchanged in both Sham-operated and SCGx mice, suggesting that the input from the SCG to CB and regions of upper airway and brainstem do not tonically regulate the baseline ventilatory parameters at rest. This finding was also supported by another study from the same group where they did not find any changes in resting baseline ventilation in C57BL6 mice with transection of the cervical sympathetic chain ( Getsy et al, 2021b ). Interestingly, these studies reported that during hypoxic challenge, SCGx mice demonstrated an attenuated ventilatory response in comparison to Sham-operated mice.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Four days after bilateral SCGx, the ventilatory parameters at rest remained unchanged in both Sham-operated and SCGx mice, suggesting that the input from the SCG to CB and regions of upper airway and brainstem do not tonically regulate the baseline ventilatory parameters at rest. This finding was also supported by another study from the same group where they did not find any changes in resting baseline ventilation in C57BL6 mice with transection of the cervical sympathetic chain ( Getsy et al, 2021b ). Interestingly, these studies reported that during hypoxic challenge, SCGx mice demonstrated an attenuated ventilatory response in comparison to Sham-operated mice.…”
Section: Discussionsupporting
confidence: 73%
“…This difference in response to hypoxia may be caused by multiple factors including the differences in animal species and the experimental time window post SCGx. Getsy et al (2021b) measured the hypoxic ventilatory response at 4 days post SCGx whereas we assessed chemoreflex function at 2 weeks post SCGx. It is possible that within 2 weeks the animals may develop some compensatory mechanisms through which adaptation to the acute loss of SCG-mediated chemoreflex modulation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The post ganglionic axons of the SCG are known to innervate the CBs ( Iturriaga et al, 2016 ). Electrical stimulation of the SCG has been shown to significantly sensitize the CB chemoreflex in hypertensive and normotensive rats ( Felippe and Paton, 2021 ; Getsy et al, 2021 ; Felippe et al, 2022 ). Therefore, an increased SCG neuronal activity during the recovery of ALI, in-part, might also contribute to chemoreflex sensitization observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The lingual nerve innervates the mucous membrane of two-thirds of the anterior area of the tongue, providing somatic and gustatory sensitivity; the nerve is anastomosed in the anterior lingual area with the sensitive fibers of the facial nerve or VII cranial nerve (cord of the eardrum), providing afferent sensitive fibers [32]. Sympathetic fibers from the superior cervical ganglion reach the tongue; this connection possibly regulates the movement of the tongue based on the oxygen present and other functions not yet fully understood [33,34].…”
Section: Review Lingual Origin and Functional Anatomymentioning
confidence: 99%